The case for citizen science in public health policy and practice: a mixed methods study of policymaker and practitioner perspectives and experiences - Leah Marks; Ben J. Smith; Jo Mitchell; Yvonne Laird; Samantha Rowbotham (BMC, 2023)
Abstract Background Citizen science (CS) is increasingly being utilised to involve the public in public health research, but little is known about whether and how CS can address the needs of policy and practice stakeholders in health promotion and chronic disease prevention. Methods Using a mixed methods approach we conducted an online survey (n = 83) and semi-structured interviews (n = 21) with policy and practice stakeholders across Australia to explore how CS approaches are perceived and applied in chronic disease prevention, how CS aligns with existing approaches to community engagement, and how the uptake of CS can be supported within policy and practice settings. Results Most participants had heard of CS, and while few had experience of using CS, there was widespread support for this approach, with many seeing it as complementary to other community engagement approaches. CS was seen as providing: (a) a robust framework for engagement; (b) access to rich data; (c) opportunities for more meaningful engagement; and (d) a mutually beneficial approach for stakeholders and community members. However, stakeholders identified a need to weigh benefits against potential risks and challenges including competing organisational priorities, resourcing and expertise, data quality and rigour, governance, and engagement. Conclusions To expand the use of CS, stakeholders identified the need for increased awareness, acceptance, and capacity for CS within public health organisations, greater access to supporting tools and technology, and evidence on processes, feasibility and impacts to enhance the visibility and legitimacy of CS approaches.